The Relationship between Emotional Disorders and Emotional Eating in Final Year Students - Dharina Baharuddin; Rahmi Ayu Fitri; Marthoenis Marthoenis; Meutia Zahara; Nurjannah Nurjannah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Emotional disorders such as anxiety, stress, and depression are prevalent among university students, particularly in their final year due to academic pressures. These conditions can influence daily behavior, including eating patterns, and may trigger emotional eating, which threatens both physical and psychological health. Self-esteem is considered a protective factor that may buffer these effects. This study aimed to examine the relationship between emotional disorders and emotional eating among final-year female students and to analyze the moderating role of self-esteem. A cross-sectional design was conducted involving 222 stu dents from Universitas Muhammadiyah Aceh. Data were collected using the DASS-21, Emotional Eating Scale (EES), and Rosenberg Self-Esteem Scale (RSES). Logistic regression analysis showed that 38.74% of respondents experienced moderate depression, 27.48% moderate anxiety, 15.77% moderate stress, and 22.17% reported emotional eating. Significant associations were found between moderate anxiety (p=0.045) and severe stress (p=0.021) with emotional eating. Moreover, self-esteem moderated the relationship between stress and emotional eating, suggesting that higher self-esteem helps students control eating behavior under stress. These findings emphasize the importance of early detection and psychosocial interventions to promote students’ mental health and healthy eating patterns.